Early growth and survival of different woody plant species established through direct sowing in a degraded land, Southern Ethiopia - Shiferaw Alem; Hana Habrova (Journal of Degraded and Mining Lands Management, 2019)
In addition to tree planting activities, finding an alternative method to restore degraded land in semi-arid areas is necessary, and direct seeding of woody plants might be an alternative option. The objectives of this study paper were (1) evaluate the growth, biomass and survival of different woody plant species established through direct seeding in a semi-arid degraded land; (2) identify woody plant species that could be further used for restoration of degraded lands. To achieve the objectives eight woody plant species seeds were gathered, their seeds were sown in a degraded land, in a randomized complete block design (RCBD) (n=4). Data on germination, growth and survival of the different woody plants were collected at regular intervals during an eleven-month period. At the end of the study period, the remaining woody plants' dry biomasses were assessed. One-way analysis of variance (ANOVA) was used for the data analysis and mean separation was performed using Fisher’s least significant difference (LSD) test (p=0.05). The result revealed significant differences on the mean heights, root length, root collar diameters, root to shoot ratio, dry root biomasses and dry shoot biomasses of the different species (p < 0.05). There were also variations among species in their germination, dry biomasses and survival. The survival of the woody plants was inversely correlated with air temperature. Of the species studied, four tree species, Dodonaea angustifolia, Vachellia tortilis, Vachellia seyal and Vachellia nilotica, were successful in growing in the degraded land; and therefore, we recommend these for restoration projects